2017
DOI: 10.5137/1019-5149.jtn.20531-17.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of unilateral versus bilateral pedicle screw fixation in transforaminal lumbar interbody fusion for single level lumbar degenerative diseases and review of literature.

Abstract: Unilateral PSF along with TLIF procedure is an effective option in selected patients.We need prospective randomized studies with higher number of patients and longer follow-up periods for more reliable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(56 reference statements)
1
5
1
Order By: Relevance
“…[5] In the study of Shen et al (2016), they reported a mean preoperative VAS of 6.8±1.6, while in the study of Işik et al (2017) they reported a mean preoperative VAS of 8.57. [6,7] In the study of Dahdaleh et al (2013), they reported a mean preoperative VAS back of 5.7±2.6, while the mean preoperative leg visual analogue score (VAS) of the studied patients in was found to be 5.7±3.1; which were less than our patients scores. [8] Chen et al (2018) found in their study that the mean preoperative ODI score was 39.0±13.35, while Kai et al (2014) found in their study that the mean preoperative ODI score was 42.4±16%.…”
Section: Discussioncontrasting
confidence: 69%
“…[5] In the study of Shen et al (2016), they reported a mean preoperative VAS of 6.8±1.6, while in the study of Işik et al (2017) they reported a mean preoperative VAS of 8.57. [6,7] In the study of Dahdaleh et al (2013), they reported a mean preoperative VAS back of 5.7±2.6, while the mean preoperative leg visual analogue score (VAS) of the studied patients in was found to be 5.7±3.1; which were less than our patients scores. [8] Chen et al (2018) found in their study that the mean preoperative ODI score was 39.0±13.35, while Kai et al (2014) found in their study that the mean preoperative ODI score was 42.4±16%.…”
Section: Discussioncontrasting
confidence: 69%
“…In agreement with our results, Chen et al [3] found a highly statistically significant difference between preoperative and postoperative scores for both back pain and leg pain at the first, sixth, and twelfth postoperative month in both groups; and, on comparing the two groups, there was a statistically significant difference regarding VAS of the back pain in the first postoperative month, which was significantly lower in unilateral group; otherwise, there was no statistically significant difference regarding VAS of the back pain throughout the follow up period. Numerous authors reported similar results, including Işik et al [13], Yang et al [25], and Villavicencio et al [22].…”
Section: Clinical Outcomesmentioning
confidence: 57%
“…Concerning the radiological outcome, numerous authors reported similar results regarding the fusion rate at 6 and 12 months postoperatively without significant difference between the two group including Chen et al [3], Işik et al [13], Villavicencio et al [22], and Yang et al [25].…”
Section: Clinical Outcomesmentioning
confidence: 79%
See 2 more Smart Citations